Bioceanic Route: an approach based on economic indicators from 2016 to 2019 - Figueiredo Fernandes Brite, Felipe (2021)
The Latin American Integration Route runs through the Bioceanic Corridor, also called road route, with the intention of connecting the Atlantic Ocean to the Pacific Ocean, passing through countries such as Brazil, Paraguay, Argentina and Chile. In this context, this article aimed to analyze the economic data of the Brazil-Paraguay stretch, focusing on the city of Porto Murtinho. It is emphasized that this work is related to the research project Bioceanic Road Corridor and University Network of the Latin American Integration Route (UniRila): The analysis verified the flows of imports and exports in a macroeconomic scenario that translated into perspectives of the corridor, presenting challenges forward as: tax rates between countries, reduction of protectionism, corruption, integration of universities and exchange. For Porto Murtinho and Carmelo Peralta, the expectation is that with the growth of the logistical flow and exports, the per capita income will increase and leverage social improvements in the municipalities.